The Impact of Political Scandals on Trust in State Institutions: Lithuanian Case Analysis - Patkauskaitė-Tiuchtienė, Inga (Politologija, 2020)
This article raises the question of whether the political scandals that take place in Lithuania have an effect on public trust in Lithuania’s state institutions and, if so, what kind of an effect can be perceived. The following institutions of the Republic of Lithuania were selected for analysis: the Government, the Parliament, the Institution of the President, the Special Investigation Service, and the State Security Department. The analysis covers the 2004–2016 years (inclusive) period. The links between political scandals and trust in state institutions are analyzed based on an institutional approach to changes in governmental trust, as well as a non-functional approach to political scandals and the results of empirical studies analyzing political scandals and their relation to governmental trust. In order to determine links between political scandals and trust in state institutions, a dynamic linear regression with time series data was performed. The analysis suggests that political scandals that took place in Lithuania during the period of 2004–2016 had a substantial impact on changes in public trust in state institutions. In the case of all institutions, a negative short-term impact of political scandals on trust in these institutions has been identified. The results of the analysis also reveal that the extent of the negative impact of political scandals may depend on the level of intensity of the escalation of political scandals in the media and the type of political scandal.